2010
DOI: 10.3103/s1066369x1001007x
|View full text |Cite
|
Sign up to set email alerts
|

Almost periodicity, finite automata mappings, and related effectiveness issues

Abstract: The paper studies different variants of almost periodicity notion. We introduce the class of eventually strongly almost periodic sequences where some suffix is strongly almost periodic (=uniformly recurrent). The class of almost periodic sequences includes the class of eventually strongly almost periodic sequences, and we prove this inclusion to be strict. We prove that the class of eventually strongly almost periodic sequences is closed under finite automata mappings and finite transducers. Moreover, an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Connections are made to kneading sequences of unimodal maps, and it is shown that a sequence A B is uniformly recurrent if and only if B is uniformly recurrent. The definitions and techniques used in this section are motivated by computer science results in [8] and [9]. Definition 4.1.…”
Section: A-uniform Schemesmentioning
confidence: 99%
“…Connections are made to kneading sequences of unimodal maps, and it is shown that a sequence A B is uniformly recurrent if and only if B is uniformly recurrent. The definitions and techniques used in this section are motivated by computer science results in [8] and [9]. Definition 4.1.…”
Section: A-uniform Schemesmentioning
confidence: 99%